Cities Surround The Countryside : Urban Aesthetics in Postsocialist China - Visser, Robin, 1962- (Book collections on Project MUSE., 2010)
Explores the cultural significance of the explosive growth of China s cities during the past three decades through interpretations of Chinese fiction, cinema, visual art, architecture, and urban design.